PENGARUH KEPERCAYAAN, KEMUDAHAN DAN KERAGAMAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN Di ONLINE SHOPPING (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
ABSTRAKNurul Awaliyah, 2016, Influence of Trust, Convenience, And Diversity Products  Against Purchase Intention Online Shopping( a case study of Students STMIK Widya Cipta Dharma Samarinda). Under the guidance of Mr. Drs. Pamasang S. Siburian, M.Agr as first counselor and Mrs Saida Zainurossalamia ZA, SE., M.Si as second counselor. The purpose of this study was to see how the Influence of variable Trust, Convenience, And Diversity Products against Purchase Intention at online shopping on student STMIK Widya Cipta Dharma Samarinda and to determine that Variable Trust, Convenience, And Diversity Products are positive and significant on the Purchase decision at online shopping of STMIK Widya Cipta Dharma Student. The analysis tool used is mutiple linear analysis. The result of this study indicate that variable Trust, Convenience, And Diversity Products are positive and significant in simultaneously against of Purchase Intention at Online Shopping, where in the F test (Simultan) and t Test (persial) had value of Fcount > Ftable (value Fcount  bigger than Ftable) Kata Kunci :Trust, Convenience, Diversity Products , Purchase Intention , Online Shopping.